Theatergarden bestiarium : The garden as Theater as Museum. - P.S.1 Contemporary Art Center Long Island; Brouwer, Marianne; Dercon, Chris; von Graevenitz, Antje; Graham, Dan; Heiss, Alana; Lamoureux, Johanna; Levinthal, David; Migayrou, Frédéric; Miller, Naomi; Schöttle, Rüdiger; Sennett, Richard (Cambridge : the MIT press, 1990)
Bazile, Bernard ; Branca, Glenn ; Coleman, James ; Daem, Hilde ; Fortuyn/O'Brien ; Gerdes, Ludger ; Graham, Dan ; Graham, Rodney ; Kasimir, Marin ; Müller, Christian Phillip ; Muñoz, Juan ; Pitz, Hermann ; Robbrecht, Paul ; Séchas, Alain ; Wall, Jeff
biog. kunstenaars en auteurs p. 170-171
Engels
Theatergarden bestiarium has been produced by The Institute for Contemporary Art, P.S. 1 Museum. The exhibition was held at P.S. 1 Museum, January 15 - March 12, 1989, and traveled to Casino de la Exposicion, Seville, June 26 - July 30, 1989, and to Confort Moderne, Poitiers, September 29 - November 29, 1989
boek